Comparative analyses of the complete genome sequences of Pierce's disease and citrus variegated chlorosis strains of Xylella fastidiosa - Van Sluys, M. A.; de Oliveira, M. C.; Monteiro-Vitorello, C. B.; Miyaki, C. Y.; Furlan, L. R.; Camargo, LEA; da Silva, ACR; Moon, D. H.; Takita, M. A.; Lemos, EGM; Machado, M. A.; Ferro, MIT; et al. (Amer Soc Microbiology, 2003)
Xylella fastidiosa is a xylem-dwelling, insect-transmitted, gamma-proteobacterium that causes diseases in many plants, including grapevine, citrus, periwinkle, almond, oleander, and coffee. X. fastidiosa has an unusually broad host range, has an extensive geographical distribution throughout the American continent, and induces diverse disease phenotypes. Previous molecular analyses indicated three distinct groups of X.fastidiosa isolates that were expected to be genetically divergent. Here we report the genome sequence of X. fastidiosa (Temecula strain), isolated from a naturally infected grapevine with Pierce's disease (PD) in a wine-grape-growing region of California. Comparative analyses with a previously sequenced X.fastidiosa strain responsible for citrus variegated chlorosis (CVC) revealed that 98% of the PD X.fastidiosa Temecula genes are shared with the CVC X. fastidiosa strain 9a5c genes. Furthermore, the average amino acid identity of the open reading frames in the strains is 95.7%. Genomic differences are limited to phage-associated chromosomal rearrangements and deletions that also account for the strain-specific genes present in each genome. Genomic islands, one in each genome, were identified, and their presence in other X.fastidiosa strains was analyzed. We conclude that these two organisms have identical metabolic functions and are likely to use a common set of genes in plant colonization and pathogenesis, permitting convergence of functional genomic strategies.